Oligosaccharides Derived from Tramesan: Their Structure and Activity on Mycotoxin Inhibition in Aspergillus flavus and Aspergillus carbonarius - Jelena Loncar; Barbara Bellich; Alessia Parroni; Massimo Reverberi; Roberto Rizzo; Slaven Zjalić; Paola Cescutti (Biomolecules, 2021)
Food and feed safety are of paramount relevance in everyday life. The awareness that different chemicals, e.g., those largely used in agriculture, could present both environmental problems and health hazards, has led to a large limitation of their use. Chemicals were also the main tool in a control of fungal pathogens and their secondary metabolites, mycotoxins. There is a drive to develop more environmentally friendly, “green”, approaches to control mycotoxin contamination of foodstuffs. Different mushroom metabolites showed the potential to act as control agents against mycotoxin production. The use of a polysaccharide, Tramesan, extracted from the basidiomycete Trametes versicolor, for controlling biosynthesis of aflatoxin B1 and ochratoxin A, has been previously discussed. In this study, oligosaccharides obtained from Tramesan were evaluated. The purified exopolysaccharide of T. versicolor was partially hydrolyzed and separated by chromatography into fractions from disaccharides to heptasaccharides. Each fraction was individually tested for mycotoxin inhibition in A. flavus and A. carbonarius. Fragments smaller than seven units showed no significant effect on mycotoxin inhibition; heptasaccharides showed inhibitory activity of up to 90% in both fungi. These results indicated that these oligosaccharides could be used as natural alternatives to crop protection chemicals for controlling these two mycotoxins.